Space lexicalization in compositions by Indonesian EFL learners: Toward near-native style - Kadarisman, A. Effendi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This research intends to find out whether Indonesian EFL learners are aware of the presence of “space” and are able to lexicalize it in their English compositions. It takes 21 seventh-semester English Department students as research subjects. They were given story pictures and asked to write a narrative. The resulting 21 EFL narratives were measured against a native-speaker narrative model in terms of “spatial words” (prepositions and adverbial particles), producing the following comparisons: 6.6% vs. 7.2% in total, 78.2% vs. 85.7% used dynamically, 95.5% vs. 100% used obligatorily, and 19.2% vs. 28.6% used in phrasal verbs. This indicates that Indonesian EFL learners are sufficiently sensitive to “space” and know how to lexicalize it in their compositions. Theoretically, their sensitivity to “space” implies that, in learning English, they have undergone some degree of cognitive restructuring; practically, EFL learners who wish to acquire a near-native writing style should be competent in space lexicalization.